Which measures of time preference best predict outcomes? Evidence from a large-scale field experiment - Stephen V. Burks; Jeffrey P. Carpenter; Lorenz Goette; Aldo Rustichini (Institute for the Study of Labor (IZA), 2011)
Economists and psychologists have devised numerous instruments to measure time preferences and have generated a rich literature examining the extent to which time preferences predict important outcomes; however, we still do not know which measures work best. With the help of a large sample of non-student participants (truck driver trainees) and administrative data on outcomes, we gather four different time preference measures and test the extent to which they predict both on their own and when they are all forced to compete head-to-head. Our results suggest that the now familiar (β, δ) formulation of present bias and exponential discounting predicts best, especially when both parameters are used.
urn:nbn:de:101:1-20110629976
Keywords: C93; D90; 330; time preference; impatience; discounting; present bias; field experiment; trucker